202k views
10 votes
Simplify the expressions.1 a. –2 t + 5 t – 2 – t

1 b. –5 z + 4 – 4 z2 a. 8 v + 3 – 10 v
2 b. –6 – 6 k – 3 – 7 k
3 a. –6 – 3 w + 4 + 10 w
3 b. 9 s + s
4 a. 6 + 8 b – 1 – 8 b
4 b. 1p + 6 + 5 – 4 p
5 a. 4 x – 3 x + 9 – 6 x5
b. 9 v + 6 v – 2 – 10 v6
a. n + 2 – (–4) n6
b. 6 n – 3 n7
a. –4 x – 4 x + 4 – 9 x7
b. –9 b + (–6) b

1 Answer

1 vote

Answer:

1 a.) 2t – 2

1 b.) –9z + 4

2 a.) –2v + 3

2 b.) –13k – 9

3 a.) 7w − 2

3 b.) 10s

4 a.) 5

4 b.) –3p + 11

5 a.) –29x + 9

b.) 15v – 60x – 2

a.) 25n + 2

b.) –15n

a.) –71x + 4

b.) –15b

Explanation:

  • NOTE: I am kind of confused about the way this question is formatted, so I tried to answer everything I could decipher.

1 a.) –2t + 5t – 2 – t → 2t – 2

1 b.) –5z + 4 – 4z → –9z + 4

2 a.) 8v + 3 – 10v → –2v + 3

2 b.) –6 – 6k – 3 – 7k → –13k – 9

3 a.) –6 – 3w + 4 + 10w → 7w − 2

3 b.) 9s + s → 10s

4 a.) 6 + 8b – 1 – 8b → 5

4 b.) 1p + 6 + 5 – 4p → –3p + 11

5 a.) 4x – 3x + 9 – 6x 5 → –29x + 9

b.) 9v + 6v – 2 – 10x 6 → 15v – 60x – 2

a.) n + 2 – (–4)n 6 → 25n + 2

b.) 6n – 3n 7 → –15n

a.) –4x – 4x + 4 – 9x 7 → –71x + 4

b.) –9b + (–6)b → –15b

User Yozi
by
4.4k points